Identification of end-users' preferences of a cassava product ("Gari") in Benue and Osun State, Nigeria - Osubade, O.A. (Ladoke Akintola University of Technology, 2020)
Breeding of improved cassava varieties has been concentrated on preferred characteristics by the farmers to the detriment of attributes preferred by other end-users which made the final product not generally acceptable by all the end users. This study aimed at identifying the preferred quality characteristics of gari/eba among farmers, processors, traders and consumers to help breeders to develop new improved cassava varieties that will meet the quality characteristics of good gari as preferred by the end-users. Four (4) communities that are major producers and consumers of gari were selected in Benue (Ty-omu, Shangevya-koti, NyamII and Al’Okete) and Osun (Oyan, Elefon, Wasimi, Ago-owu) States. Purposive sampling technique was used to collect information from 110 respondents in Benue and 109 in Osun through Focus group discussions, individual interviews and market interview among the farmers, processors, and traders using a well-structured questionnaire. Four selected cassava varieties (TMS-IBA011412, TMS14F1278PP0003, TMS14F1022P0003, atu/ banada) were processed to gari and turned to eba (using ratio 1:3 gari/water) for consumer’s acceptability. A well structured questionnaire comprising of 9-points hedonic test, Just About Right test (JAR) and Check-All-That-Apply test (CATA) was administered to 300 consumers for consumer acceptability. Data collected were subjected to statistical analysis using statistical package for social scientist (SPSS) and xlstat package. The results showed that the most preferred traits in cassava by Benue State farmers are dense root, low moisture roots, white-flesh root, non-decaying root, big long roots, non-woody roots and 8-15 roots per stand. Processors prefer non-decaying roots, white mash with low moisture, and gari that is white and dry, non-coarse, and gelatinize faster. Marketers/ consumers prefer dry, bright/shiny, white, sweet, dense, fine, cooked aroma and sour gari. Osun State respondents revealed that farmers prefer dense root, non-decaying root, white-flesh root, high dry matter roots, big-long roots, 8-16 roots per stand and non-woody roots while processors prefer non-decaying roots, white mash with low moisture, and gari that is non-coarse, dry, white and gelatinize easily. Marketers/ consumers prefer dry, white, dense, sour, and fine gari. Key user-preferred quality traits for gari in both regions were dry gari followed by white, dense, fine, sour, bright/shiny and aroma and sweet gari in that order. In comparison, in-term of taste and appearance of gari, consumers in Osun State prefer sour and white gari while Benue State consumers did not like sour gari but preferred sweet and shiny gari. The results of the consumer’s acceptability showed the frequencies of the good characteristics of final product (eba) in Benue and Osun State. The frequencies of good characteristics mentioned by Benue consumers on most preferred eba sample produced from banada showed that neatness had the highest with frequency of 146 out of 150 consumers, followed by smoothness (143), good taste (143), mouldable (140), good aroma (138), stretchy (137), white (126), moderately soft (116), fermented odour (79), not sour (78), and less lump (60). The frequencies of good characteristics mentioned by Osun consumers on most preferred eba sample made from atu showed that mouldable had the highest with frequency of 150 out of 150 consumers, followed by neatness (148), good taste (141), good aroma (140), smoothness (140), stretchy (133), moderately soft (127), sour (116), cream (90), fermented odour (64), white (39). The information presented in this work with an in-depth laboratory characterization of the raw roots and the product is essential to identify product profiles within breeding. The findings will help breeders to develop improved cassava varieties that will be acceptable by multi end-users.